Comparative study of the airborne microbial communities and their functional composition in fine particulate matter (PM2.5) under non-extreme and extreme PM2.5 conditions. (December 2018) - Abd Aziz, Azilah; Lee, Kwangyul; Park, Byeonghyeok; Park, Hongjae; Park, Kihong; Choi, In-Geol; Chang, In Seop
Abstract: Asian dust (AD) events increase environmental pollution and have a detrimental effect on human health. Particulate matter with an aerodynamic diameter <2.5 μm (PM2.5 ) and containing airborne microorganisms increases during AD events due to the transportation of dust by wind from several arid regions in China. This study analyzed the bacterial and fungal communities associated with average daily PM2.5 concentrations less than (on non-event day: ND) and exceeding (on event day: ED) the air quality standard (36 μg PM2.5 m -3 ) set by the Korean government. The taxon compositions and functional genes of airborne microorganisms were assessed using shotgun metagenomics sequencing and metagenome rapid annotation using subsystem technology (MG-RAST) analysis. MG-RAST is an open source web application, serving as a platform that automatically analyzes uploaded metagenomes. During ND, 51% of total bacteria sequences consisted of those from Proteobacteria, which were closely related to nitrogen-fixing bacterial species. A high percentage of functional genes consisted of those genes related to nitrogen metabolism, suggesting that the airborne microorganisms are associated with environmental nitrogen cycles. During ED, 57% of total bacteria sequences consisted of those from Bacteroidetes, accompanied by high relative abundance of sequences from pathogenic species of Bacillus and Staphylococcus . Fungal sequences were mainly composed of those from the phyla Ascomycota and Basidiomycota, which include spore-forming species transported frequently by wind. The abundance of Ascomycota sequences was higher in ED (81%) than in ND (22%) samples, and mainly included those from the plant pathogens Phaeosphaeria and Pyrenophora . These findings indicated that microbial composition shifted from ND to ED samples, even at the phylum level. This switch was likely due to the sources of dust particles, with those during ED being primarily from arid regions in Mongolia and industrial regions in China. Additional studies are required to further understand the diversification of airborne microbial communities in downwind areas. Graphical abstract: Highlights: The bacterial community differed between non-event (ND) and event days (ED). Proteobacteria dominated during ND, while Bacteroidetes dominated during ED. Ascomycota were highly abundant, especially during ED. Several pathogenic genera were identified, and proportion was higher during ED. Functional genes related to nitrogen metabolism were abundant during ND.